The Nutritional Content of Fish Meal from Bycatch in Batu Beriga Village, Bangka Belitung - Sudirman Adibrata; Denny Syaputra; Robet Perangin-angin; Devi Wulansari; Kim V Van (Marine Science Department Diponegoro University, 2022)
Bycatch has the added value of being processed into meals for animal feed or fish farming needs. Therefore, this study aims to determine the nutritional content of local fish meals from the bycatch in Batu Beriga Village, Bangka Belitung. The method used for processing fish meal was a wet mill from bycatch. Quality parameters referred to the Indonesian National Standard (SNI) 01-2715-1996/Rev.92 regarding fish meal as raw material for feed. The results showed that 4 kg of wet fish could produce a meal of 0.4 kg. The nutritional content of the local fish meal is of high quality as it met the requirements of SNI Quality I, II, and III, allowing it to be released to the market. The laboratory tests showed water, ash, crude protein, crude fat, crude fiber, calcium, phosphorus, NaCl, Gross energy, Carbohydrate, and pH content of 5.06% (SNI Quality I maximum 10%), 18.51% (SNI Quality I maximum 20%), 68.13% (SNI Quality I minimum 1.5%), 5.71% (SNI Quality I maximum 20%), 1.54% (SNI Quality I maximum 8%), 4.09% (SNI Quality I range 2.5-5.0%), 6.82% (SNI Quality I range 1.6-3.2%), 1.78% (SNI Quality I maximum 2%), 4,609.67 Kcal/kg, 0.0%, and 6, respectively. Furthermore, amino acids from a local fish meal could be used as feed mixtures for aquaculture. Bycatch can be used to fish meals as a potential side business for fishers. In sustainable fisheries development, independence in animal feed should be established immediately, hence the dependence on other regions can be minimized.